Contemporary Irish Writing and Environmentalism The Wearing of the Deep Green - Potts, Donna L. (New Directions in Irish and Irish American Literature, 2018)
This book examines how the Irish environmental movement, which began gaining momentum in the 1970s, has influenced and been addressed by contemporary Irish writers, artists, and musicians. It examines Irish environmental writing, music, and art within their cultural contexts, considers how postcolonial ecocriticism might usefully be applied to Ireland, and analyzes the rhetoric of Irish environmental protests. It places the Irish environmental movement within the broader contexts of Irish national and postcolonial discourses, focusing on the following protests: the M3 Motorway, the Burren campaign, the Carnsore Point anti-nuclear protest, Shell to Sea, the turf debate, and the animal rights movement.